IMPLEMENTASI KOMANDO STRATEGIS PEMBANGUNAN PERTANIAN (KOSTRATANI) DI BPP KECAMATAN PAYAKUMBUH KABUPATEN LIMA PULUH KOTA - Sidra Nefi; Gunarif Taib; Asmawi Asmawi (Agros Journal of Agriculture Science, 2023)
This study aims to identify and describe the implementation of the Kostratani program at BPP Payakumbuh District, Lima Puluh Kota District, to analyze the achievements of the implementation of the Kostratani program at BPP Payakumbuh District, Lima Puluh Kota District. This research is a qualitative research with the type of case study research, carried out from August to December 2022. The selection of locations and informants was carried out purposively (intentionally). Data analysis used descriptive qualitative analysis. From the research results it can be identified that the development of BPP Kostratani in BPP Payakumbuh District and the implementation of the functions and roles of BPP as a data center, center for the agricultural development movement, learning center are in accordance with the indicators in the Kostratani SOP. Meanwhile, BPP as an agribusiness consulting center and partnership network center has not been implemented according to the indicators in the Kostratani SOP. The implementation of Kostratani development at BPP Payakumbuh District has been supported by IPDMIP activities but has not yielded good results. BPP Payakumbuh Sub-District has only been able to implement four of the six BPP Kostratani indicators, the implementation of which has not been optimal because there is no commitment from implementers at the Kostrawil, Kostrada and Kostratani levels in the sub-district. The implementation of Kostratani has not been supported by resource capabilities in the form of human resources and facilities owned by BPP.  Keywords: Kostratani; BPP; Implementation. INTISARIPenelitian ini bertujuan untuk mengidentifikasi dan mendeskripsikan pelaksanaan program Kostratani di BPP Kecamatan Payakumbuh Kabupaten Lima Puluh Kota, untuk menganalisis capaian pelaksanaan implementasi program Kostratani di BPP  Kecamatan Payakumbuh Kabupaten Lima Puluh Kota. Penelitian ini merupakan penelitian kualitatif dengan jenis penelitian studi kasus, dilaksanakan bulan Agustus sampai dengan Desember 2022. Pemilihan lokasi dan informan dilakukan secara purposive (sengaja). Analisis data menggunakan analisis deskriptif kualitatif. Dari hasil penelitian dapat diidentifikasi bahwa pengembangan BPP Kostratani di BPP Kecamatan Payakumbuh dan pelaksanaan fungsi dan peran BPP sebagai pusat data, pusat gerakan pembangunan pertanian, pusat pembelajaran sudah sesuai indikator dalam SOP Kostratani. Sedangkan BPP sebagai pusat konsultasi agribisnis dan pusat jejaring kemitraaan belum dilaksanakan sesuai indikator dalam SOP Kostratani. Pelaksanaan pengembangan Kostratani di BPP Kecamatan Payakumbuh sudah di dukung oleh kegiatan IPDMIP tapi belum memberikan hasil yang baik. BPP Kecamatan Payakumbuh baru mampu melaksanakan empat dari enam indikator BPP Kostratani pelaksanaannya belum optimal karena tidak adanya komitmen dari implementor di tingkat Kostrawil, Kostrada dan Kostratani di kecamatan. Pelaksanaan Kostratani belum di dukung kemampuan sumberdaya berupa sumber daya manusia, dan fasilitas yang dimiliki oleh BPP. Kata Kunci : Kostratani; BPP; Implementasi.